Double trouble, managing bilateral inflammatory breast cancer: a case report - Sabaté-Ortega, Josep; Ribera-Montserrat, Anna; del Barco, Sonia; Roqué-Lloveras, Ariadna; Fort-Culillas, Roser; Carmona-García, M. Carme; Liñan, Raquel; Polonio-Alcalá, Emma; Carbó-Vilavedra, Gerard; Ramos-Oliver, Irma; Bujons-Buscarons, Elisabet; Montañés-Ferrer, Claudia; et al. (Frontiers in Oncology, 2025)
Inflammatory breast cancer (IBC) is a rare and aggressive breast cancer type, accounting for 5-7% of breast cancer-related deaths, and its bilateral involvement is exceedingly uncommon. We report a case of metachronous bilateral IBC in a 50-year-old premenopausal woman with Charcot-Marie-Tooth disease, offering novel insight into the diagnostic, therapeutic, and molecular challenges of this condition. The patient initially presented with acute right breast erythema, skin thickening, and peau d’orange, followed by contralateral breast involvement with similar symptoms. Disease progression occurred with changes in receptor status and eventual loss of hormone receptor (HR) expression. The initial diagnosis was stage IIIB HR-positive/HER2-negative IBC. The patient underwent neoadjuvant chemotherapy, surgery, adjuvant radiotherapy, and endocrine therapy. However, the patient experienced a contralateral recurrence after 11 months of disease-free survival. Subsequent management involved multiple systemic therapies, including targeted therapy after next-generation sequencing analysis revealed a PIK3CA mutation. Although some clinical benefit was achieved, the disease continued to progress. Ultimately, the patient passed away four years after the initial diagnosis. This case underscores the aggressive and recurrent nature of bilateral IBC, its diagnostic complexity, and the importance of molecular profiling in guiding targeted treatment. It highlights the need for clinical vigilance, timely reassessment of tumor biology, and individualized multimodal care in managing rare and evolving presentations of IBC.